Pengaruh Penggunaan Biochar Berbahan Sufmuti (Chromolaena odorata) dan Teh Kompos Berbahan Ekskreta Ayam terhadap Kandungan Nutrien Rumput Odot (Pennisetum purpureum cv. Mott) - Irmalis B. Watu; Oktovianus R. Nahak (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
The research was conducted in 2 locations; namely, the cultivation process took place at the Experimental Garden belonging to the Animal Husbandry Study Program, Faculty of Agriculture, University of Timor, while the analysis of nutritional content was carried out at the Laboratory of Feed Chemistry, University of Nusa Cendana, Kupang. The study lasted for one period (60 DAS) and started from May to the end of June 2020. The study aimed to determine the best level of biochar use on the nutrient value of odot grass, determine the best dosage of compost tea use on the nutrient value of odot grass, and determine whether there is an interaction with the administration of biochar and compost tea. This research is an experimental study using a completely randomized design (CRD) with a 3x3 factorial pattern repeated three times so that there are 27 experimental units. The treatments tested consisted of Lo = Without Biochar L1 = Biochar 100g L2 = Biochar 200g and Do = Without Compost Tea D1 = Dose 150 ml D2 = Dose 300 ml. The variables observed in this study were dry matter content (DM), organic matter content (BO), and crude fiber content (SK). (1) The results showed that the 200 g biochar level produced the best dry matter. (2) A 300 ml compost tea dosage produces the best dry matter, organic matter, and crude fiber. (3) There is an interaction with the level of biochar and the dose of compost tea to produce a good plant height. It can be concluded that (1) Biochar Level 200 g produced the best dry matter and crude plant fiber content. (2) Giving a dosage of compost tea of 300 ml/pot can produce the best organic material content. (3) There was an interaction between biochar level (200 gr/pot) and compost tea (300 ml/pot) on dry matter. Watering treatment Once seven days of compost tea has been effective against the nutritional content of odot grass.